Cytotoxic and genotoxic effects mediated by M2 muscarinic receptor activation in human glioblastoma cells. (November 2015) - Di Bari, Maria; Tombolillo, Vanessa; Conte, Claudia; Castigli, Emila; Sciaccaluga, Miriam; Iorio, Egidio; Carpinelli, Giulia; Ricordy, Ruggero; Fiore, Mario; Degrassi, Francesca; Tata, Ada Maria
Abstract: Glioblastomas are the most common brain tumors in humans. Previously, we demonstrated that the muscarinic receptor agonist, arecaidine propargyl ester, via M2 receptors, inhibits cell proliferation in a time and dose-dependent manner and induces a severe apoptosis in human U251 and U87 glioblastoma cell lines. In order to clarify the mechanisms causing apoptosis after arecaidine treatment, we analyzed the ability of arecaidine to induce oxidative stress. By dichloro-dihydro-fluorescein diacetate (DCFDA) staining, we demonstrated that arecaidine increased the intracellular ROS levels. ROS accumulation was completely counteracted by the ROS scavenger, N-acetyl-l -cysteine (NAC). Apoptotic cell death appeared directly correlated to ROS production since NAC was able to counteract this effect. Although there was an up-regulation of some detoxifying enzyme expression such as superoxide dismutase (MnSOD) and sirtuin-1 (SIRT1), the cytotoxic effect caused by arecaidine treatment caused DNA damage, as demonstrated by the increase of histone γ-H2AX positive cells, and chromosomal aberrations. These effects were mediated by M2 receptor activation; in fact after silencing of M2 receptors by siRNA, the increase of γ-H2AX positive cells was abolished. In conclusion, in addition to a cytostatic effect previously described, in the present study we have better characterized the mechanisms causing the cytotoxic effects and the apoptotic cell death in glioblastoma cells after M2 receptor activation. These data allow to consider this receptor a new interesting therapeutic tool for the glioblastoma treatment. Highlights: The M2 receptors activation counteracts cell proliferation and survival in glioblastoma. M2 receptors appear an interesting therapeutic tool in glioblastoma therapy. More selective M2 receptor ligands may represent a new promising therapeutic perspective.